2017
DOI: 10.1371/journal.pone.0173686
|View full text |Cite
|
Sign up to set email alerts
|

Changes in salivary microbiota increase volatile sulfur compounds production in healthy male subjects with academic-related chronic stress

Abstract: ObjectiveTo investigate the associations among salivary bacteria, oral emanations of volatile sulfur compounds, and academic-related chronic stress in healthy male subjects.Materials and methodsSeventy-eight healthy male undergraduate dental students were classified as stressed or not by evaluation of burnout, a syndrome attributed to academic-related chronic stress. This evaluation was carried out using the Maslach Burnout Inventory—Student Survey questionnaire. Oral emanations of hydrogen sulfide, methyl mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
2
23
1
4
Order By: Relevance
“…In previous work, we found that coculturing of F. nucleatum and S. moorei produced higher H 2 S values than S. moorei or F. nucleatum grown individually (Nani et al., ). It can be concluded from the results obtained here and in our previous data that the two bacteria work together in the process leading to halitosis, with S. moorei probably deglycosylating mucin, which is then degraded by F. nucleatum, promoting the formation of VSCs (Sterer & Rosenberg, ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In previous work, we found that coculturing of F. nucleatum and S. moorei produced higher H 2 S values than S. moorei or F. nucleatum grown individually (Nani et al., ). It can be concluded from the results obtained here and in our previous data that the two bacteria work together in the process leading to halitosis, with S. moorei probably deglycosylating mucin, which is then degraded by F. nucleatum, promoting the formation of VSCs (Sterer & Rosenberg, ).…”
Section: Discussionmentioning
confidence: 77%
“…Recently, we showed that healthy stressed male undergraduate students experiencing chronic academic stress presented increased oral H 2 S emanations, which were associated with increased salivary levels of S. moorei and its coexistence with F. nucleatum (Nani et al., ). The findings indicated that the altered saliva composition in chronically stressed subjects provided a more favorable environment for H 2 S production in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently reported in research targeting healthy male dental students that chronic academic‐related stress increases the concentrations of H 2 S and CH 3 SCH 3 , and is associated with higher salivary S . moorei levels (Nani et al, ). Oral dryness and necrotic ulcers in patients with cell carcinoma of the oral cavity also cause oral malodor.…”
Section: Induction Of Oral Malodormentioning
confidence: 99%